Generalisation of Community Empowerment in the Viewpoint of Jasser Auda's Maqashid Shari'ah: A Study on Underdeveloped Villages in Lombok Island, West Nusa Tenggara - Taqwiem, Ahsani; Rachmadi, Kartika Rose (ITB AAS INDONESIA Surakarta, 2024)
This research is a qualitative research with a case study approach to answer the strategies used in empowering disadvantaged rural communities, strategies used to manage tourism productive alms-based and strategies for empowering disadvantaged rural communities through alms-based tourism from the maqāṣid al-sharī'ah perspective. Data collection techniques using observation, interviews, and documentation. The results of this study indicate that the strategies implemented in empowering disadvantaged rural communities in Sambik Bangkol village are by motivating, discution, providing training, providing business capital and finally business assistance. The strategies carried out in the management of productive alms-based tourism are strengthening local movements, collaborating with BAZNAS and the tourism office, procuring study visits to tourist villages, and fostering human resources.While empowering disadvantaged rural communities through productive alms-based tourism, the maqāṣid al-sharī'ah perspective is able to fulfill the four aspects contained in maqāṣid al-sharī'ah, including maintaining religion (ḥifẓ addīn) by maintaining fardhu prayers, paying ZIS and also holding tahlil filled with Maqashid Syariah